The scientific production of Brazilian neurologists: 1995-2004 Produção científica dos neurologistas brasileiros: 1995-2004 - Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
The Brazilian scientific production saw more than a four-fold increase from the 1990s onwards. The aim of this study was to evaluate the evolution of scientific production by Brazilian clinical neuroscientists over the last 10 years. A search in the PubMed identified 295 clinical neuroscientists and their publications. Brazilian production corresponded to 2.37% of the papers published by the 20 indexed periodicals that regularly publish clinical neuroscience research. If only the first and last two years are compared, there was a real growth of 75.1%. More than 40% of the Brazilian papers were published in Arquivos de Neuro-Psiquiatria, the official journal of the Brazilian Academy of Neurology. When only those periodicals with impact factor higher than one are considered, the percentage falls to 0.86% in the whole 10-year period, but attains 1.23% in 2004. Epilepsy and infectious diseases were the sub-areas with the highest scientific production. A produção científica brasileira mais do que quadruplicou desde 1990. O objetivo deste estudo foi avaliar a evolução da produção dos neurocientistas clínicos brasileiros nos últimos 10 anos. Pesquisa realizada no PubMed identificou 295 neurocientistas clínicos e suas publicações. A produção brasileira representou 2,37% dos artigos publicados pelos 20 periódicos indexados que regularmente publicam pesquisas em neurociência clínica. Quando somente os primeiros e últimos dois anos forem comparados houve crescimento real de 75,1%. Mais de 40% dos artigos brasileiros foram publicados em Arquivos de Neuro-Psiquiatria, o jornal oficial da Academia Brasileira de Neurologia. Quando apenas periódicos com fator de impacto superior a 1 foram considerados, a porcentagem caiu para 0,86% no período total, mas atingiu 1,23% em 2004. Epilepsia e doenças infecciosas foram as subáreas com a maior produção científica.